Evaluación del rendimiento de un prototipo de máquina picadora para la obtención de elementos triturados a partir de la cáscara de maní (Arachis hypogaea L.) - Viñan Capa, Solage Micaela (2024)
This paragraph discusses the peanut shell, which is a harvest residue that is easily disposed of. It is rich in organic matter and nutrients, making it a potential soil improvement source. To manage this residue effectively, machinery is necessary to reduce labor and optimize time. The curricular integration project aimed to evaluate the performance of a prototype shredding machine for obtaining crushed elements from peanut shells (Arachis hypogaea L.). Additionally, the resulting material was characterized for its role in soil decomposition and enhancement at the Quinta Experimental La Argelia of the UNL. The study followed an experimental research design with two phases: first, measuring the machine’s processing capacity and performance, and then sieving the resulting material with diameters of 4, 8, and 10 mm. Subsequently, a completely randomized experimental design was employed, including four treatments. The sieved material and a control group without residue application were tested in a loamy soil during the cultivation of Cherry tomatoes (Solanum lycopersicum). The results indicated that the shredding machine prototype was moderately efficient, with only 67% of the material being crushed and low fuel consumption. The machine rental fee was affordable and included operator costs. However, the chemical composition of the crushed material hindered natural decomposition, with the 4 mm particles showing the closest proximity to this process. Regarding soil improvement, the pH, organic matter, bulk density, and porosity were evaluated. Among the particle sizes tested, the 10 mm particles had the most significant impact on increasing both pH and porosity, while the 4 mm particles contributed the most organic matter. In terms of substrate application, tomato plant height was similar across all treatments, but 8 mm particles resulted in taller plants. The study concluded that the shredding machine prototype is a viable alternative for generating fertilizers and materials that enhance soil conditions using peanut shells